STRATEGI KOMUNIKASI KOMISI PEMILIHAN UMUM (KPU) KABUPATEN SERAM BAGAN TIMUR DALAM PEMILIHAN KEPALA DAERAH DI PANDEMI COVID-19 - Rido Latuheru; Alma Ali Jamaludin (JURNAL BADATI, 2022)
This study aims to analyze the communication strategy of the General Election Commission (KPU) of SBT Regency in the regional headelection during the COVID-19 pandemic. The researcher uses a qualitative research type with the research subject of SBT Regency KPU, HR Division and community participation. The results showed that the communication strategy of the SBT Regency General Election Commission (KPU) in managing the Regional Head Election(PILKADA) during the Covid-19 Pandemic was in accordance with Walter Shewhart's theory, namely: (1) Plan, in terms of planning to manage Pilkada during the Covid-19 pandemic. 19 SBT Regency KPU is regulated by PKPU Number 5 of 2020 and technical implementation is regulated by PKPU Number 6 of 2020, (2) Do, in the Implementationof Pilkada during the Covid-19 pandemic, the SBT Regency KPU is in accordance with PKPU Number 5 of 2020 which all stages of the Pilkada are carried out using the Covid-19 prevention and spread protocol, (3) Check, after designing and implementing it, the thing that needs to be done to know in depth the problems in the field is toevaluate. The SBT Regency KPU in managing and carrying out the Pilkada during the pandemic also encountered problems at the stages of the Pilkada. One of them is the violation of health protocols at the time of registration for candidates for regent and deputy regent. However, the problem is immediately evaluated so that at the next stage the SBT Regency KPU can fix it, (4) Act, after going through the evaluation process then proceed with the follow-up process, in this process it can be in the form of modifying the problem, revising the process or changing policies.